Effect of Coffee on Caloric Expenditure in College-Aged Adults During Moderate Exercise - Gutzman, Nicole; Meitzen, Maggie; Moy, Tiffany; Wick, Casey (My University, 2013)
The purpose of this study was to measure the effects on caloric expenditure of consuming caffeinated and decaffeinated coffee prior to an exercise session.
Color poster with text, photographs, and tables.
Keywords: Caloric expenditure; Exercise; Coffee--Effects of; Posters